Prevalence and sociodemographic factors associated with loneliness and depression among older adults - Syed Elias, Sharifah Munirah ([s.n.], 2011)
ABSTRACT Background/Objective The phenomenon of loneliness exists in people of all ages but may cause a problem to older adults. On the other hands, depression has long been acknowledged to be a serious mental health problem in the older adult population. Nevertheless, diagnosing depression in the older adult is often difficult. The aim of this study is to determine prevalence and sociodemographic factors associated with loneliness and depression among older adults. Methods This is a cross sectional survey design and was carried out at the outpatient clinics of UMMC. All older adults (age 65 years old and above) has been recruited as a sample through convenience sampling. The calculated sample size is 406 respondents. The questionnaire has been self administered by the respondents. The instrument used is a questionnaire that consists of sociodemographic, UCLA loneliness scale and M-GDS-14. MMSE has been used for cognitive screening. Statistical test (two-tailed, statistically significant at p < 0.05) has been analyzed as descriptive and inferential (Chi-squared test, Fisher‟s exact test and Binary logistic regression analysis). Ethical considerations from medical ethical committees and informed consent have been performed. Pilot study has been conducted with the Cronbach‟s alpa 0.770 and 0.734. Results The response rate of the study is 98%. The prevalence of loneliness and depression among older adults are 41.2% and 18.7% respectively. Race (p<0.000), educational level (p<0.000) and living arrangement (p<0.003) were found significantly associated with loneliness. Meanwhile, educational level (p<0.000), income (p<0.046) and loneliness (p<0.001) were found significantly associated with depression. The predictors of loneliness are non-Malay (AOR 7.20 95%CI 4.35, 11.89), living alone (AOR 4.49 95%CI 1.46, 13.80) and primary school education/none (AOR 2.29 95%CI 1.40, 3.74) whereas the predictors of depression are lonely (AOR 2.28 95%CI 1.31, 3.49) and primary school education/none (AOR 4.14 95%CI 2.28, 7.52). Conclusion Loneliness and depression is very common among older adults. With the high prevalence of loneliness and depression among older adults, this is important problems that need to be addressed at outpatient‟s clinic.